Design of a Transmission Mution Measurement System in Single Mode Cable Index and Multi Step Index Step Optical Models Due to Bending Data Factors with Fingers Using OPM and OTDR Measurement Equipment - Hadria Octavia; Aprinal Adila Asril; Vera veronica; Shara Khairunnisa (Jurnal Ilmiah Poli Rekayasa, 2019)
Warping that occurs in fiber optik cables has the potential to cause serious power losses and further leads to optikal fiber rupture. Therefore, it is necessary to measure the effect of the optikal fiber curvature on the power loss generated when the optikal fiber is curved. This study aims to determine changes in the intensity of light output through plastic optikal fibers. this research distinguish the type of single mode cable and multi mode with varying radius. This paper only discusses the calculation of light output that has been affected by the curve of the optikal fiber. from the analysis conducted with a fiber optik cable length of 100 m, attenuation of 0.001 db / km and a bending radius that varies with a bend radius of 8 cm, 2x4 cm and 4 cm. different optikal fiber warping losses are obtained. that single mode cable is better than multimode cable. Kata Kunci : Serat Optik,bending, Redaman, Jari-Jari, Singel mode, Multi mode